Characterisation of a split gradient coil design induced systemic imaging artefact on 0.35 T MR-linac systems. (1st July 2023) - Marage, Louis; Walker, Paul-Michael; Boudet, Julien; Fau, Pierre; Debuire, Pierre; Clausse, Emmanuelle; Petitfils, Aurélie; Aubignac, Léone; Rapacchi, Stanislas; Bessieres, Igor
Abstract: Objective . The aim of this work was to highlight and characterize a systemic 'star-like' artefact inherent to the low field 0.35 T MRIdian MR-linac system, a magnetic resonance guided radiotherapy device. This artefact is induced by the original split gradients coils design. This design causes a surjection of the intensity gradient in Z (or head-feet) direction. This artefact appears on every sequence with phase encoding in the head-feet direction. Approach . Basic gradient echo sequence and clinical mandatory bSSFP sequence were used. Three setups using manufacturer provided QA phantoms were designed: two including the linearity control grid used for the characterisation and a third including two homogeneity control spheres dedicated to the artefact management in a more clinical like situation. The presence of the artefact was checked in four different MRidian sites. The tested parameters based on the literature were: phase encoding orientation, slab selectivity, excitation bandwidth (BWRF ), acceleration factor (R) and phase/slab oversampling (PO/SO). Main results . The position of this artefact is constant and reproducible over the tested MRIdian sites. The typical singularity saturated dot or star is visible even with the 3D slab-selection enabled. A management is proposed by decreasing the BWRF, the R in head-feet direction and increasing the PO/SO. The oversampling can be optimized using a formula to anticipate the location of artefact in the field of view. Significance . The star-like artefact has been well characterised. A manageable solution comes at the cost of acquisition time. Observed in clinical cases, the artefact may degrade the images used for the RT planning and repositioning during the treatment unless corrected.